2018
DOI: 10.1111/aos.13981
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral pigmentary retinopathy: a retrospective case series

Abstract: Purpose To review the clinical characteristics and address the aetiology in a group of patients presenting with unilateral retinal pigmentary changes, best described as unilateral pigmentary retinopathy (UPR). Methods The cohort of 42 patients was identified retrospectively from the Moorfields Eye Hospital electrophysiology database. All had undergone full‐field [electroretinography (ERG)] and pattern electroretinography (PERG), with 13 additionally having multifocal ERG (mfERG). The clinical findings, fundus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In patient 2 the ffERG was affected in both eyes, demonstrating a bilateral retinal dystrophy. Similarly, Errera et al reported 42 patients with URP, where eight patients had subnormal ffERG findings in the fellow eye [ 4 ]. The chorioretinal atrophic changes in the peripapillary area along with increased autofluorescence in the right eye of patient 2 might indicate an asymmetric presentation of a bilateral RP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In patient 2 the ffERG was affected in both eyes, demonstrating a bilateral retinal dystrophy. Similarly, Errera et al reported 42 patients with URP, where eight patients had subnormal ffERG findings in the fellow eye [ 4 ]. The chorioretinal atrophic changes in the peripapillary area along with increased autofluorescence in the right eye of patient 2 might indicate an asymmetric presentation of a bilateral RP.…”
Section: Discussionmentioning
confidence: 99%
“…Two possible genetic mechanisms have been suggested to play a role in asymmetrical RP or URP, namely, mosaicism and somatic mutations during embryogenesis. However, the exact pathogenesis and genetic mechanism are currently unclear [ 1 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pattern ERG P50 was used to assess macular function and darkadapted (DA) and light-adapted (LA) full-field ERGs were used to assess generalised rod and cone system function; the LA 30Hz flicker ERG peak time was examined and plotted separately, as established in previous studies as a sensitive measure of retinal dysfunction in BRC [9,10]. Pattern and full field ERGs obtained before and after treatment were compared and plotted as a percentage of the lower limit of normal, the latter defined as the lowest amplitude in a control group, minus 5% of the reference interval [17]. In all but one case PERG and ERG were performed prior to treatment with Ozurdex ® and/or FAc implant with a mean follow-up of 26 months (median 24.5 months; range 10-54 months).…”
Section: Angiographic and Electrophysiological Testing Protocols Andmentioning
confidence: 99%